EFFECT OF KNOWLEDGE MANAGEMENT AND TALENT MANAGEMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE - Sitti Rizki Mulyani; Muhammad Ridwan; Rio Andhika Putra; Vicky Brama Kumbara; Yulanda Putri (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background: This study aims to examine how much influence knowledge management and talent management have on the performance of general bureau employees at the West Sumatra Governor's Office with job satisfaction as an intervening variable. Method: collecting data by distributing questionnaires, with a sample of 60 respondents. The analytical method used is SMART PLS 3.0. Result: results of this study are (I) Knowledge management has a positive and significant effect on job satisfaction. (II) Talent management has a positive and significant effect on job satisfaction. (III) Knowledge management has a positive and significant effect on employee performance. (IV) Talent management has a positive and non-significant effect on employee performance. (V) job satisfaction has a positive and significant effect on employee performance. (VI) Knowledge management has a positive and significant effect on employee performance through job satisfaction. (VII) Talent management has a positive and insignificant effect on employee performance through job satisfaction. Conclution: contribution of knowledge management and talent management variables to employee performance is 5%. The contribution of knowledge management and talent management variables to job satisfaction is 86%.